1997
DOI: 10.2105/ajph.87.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among runaway and homeless youth in three national samples.

Abstract: OBJECTIVES: Standardized estimates of the prevalence of substance use by runaway and homeless youth between the ages of 12 and 21 in various settings were compared with each other and with estimates for youth in the general population. METHODS: Four surveys were used: (1) a nationally representative survey of runaway and homeless youth residing in federally and non-federally funded shelters; (2) a multicity survey of street youth; (3) a nationally representative household survey of youth with and without recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
162
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(173 citation statements)
references
References 12 publications
11
162
0
Order By: Relevance
“…4 Population-based studies have shown that homeless and marginally housed youth report exhibit significant behavioral health disparities compared to stably housed youth, including depression 7,8 and substance use. 7,9 Much of the disparities exhibited by youth experiencing homelessness have been attributed to past early and background negative life experiences. [10][11][12][13] Numerous studies using community-based samples of homeless youth have documented that sexual minority youth are more likely to experience homelessness, and homeless sexual minority youth report greater risk for mental health and substance abuse symptoms than homeless heterosexual youth, [14][15][16][17][18][19] yet few among these have assessed determinants that help explain the disparities between sexual minority youth and heterosexual youth experiencing homelessness.…”
mentioning
confidence: 99%
“…4 Population-based studies have shown that homeless and marginally housed youth report exhibit significant behavioral health disparities compared to stably housed youth, including depression 7,8 and substance use. 7,9 Much of the disparities exhibited by youth experiencing homelessness have been attributed to past early and background negative life experiences. [10][11][12][13] Numerous studies using community-based samples of homeless youth have documented that sexual minority youth are more likely to experience homelessness, and homeless sexual minority youth report greater risk for mental health and substance abuse symptoms than homeless heterosexual youth, [14][15][16][17][18][19] yet few among these have assessed determinants that help explain the disparities between sexual minority youth and heterosexual youth experiencing homelessness.…”
mentioning
confidence: 99%
“…Research shows that homeless young people participate in numerous substance use related behaviors including illicit drug and alcohol use (Koopman et al, 1994;Greene et al, 1997;Bailey et al, 1998;Kipke et al, 1998;Chen et al, 2004;Van Leeuwen et al, 2004), injecting drugs and/or needle sharing (Greene et al, 1997;Kral et al, 1997;Bailey et al, 1998;Kipke et al, 1998), selling drugs (Hagan and McCarthy, 1997;, and receiving treatment for substance abuse problems (Smart and Ogborne, 1994;.…”
Section: Substance Use Related Behaviormentioning
confidence: 99%
“…Similarly, risky substance use related behaviors also vary by gender (Warheit and Biafora, 1991;Anderson et al, 1994;Greene et al, 1997;MacKellar et al, 2000), sexual orientation (Moon et al, 2000), age (Van Leeuwen et al, 2004), and the frequency with which youth run from home and/or spend time on the street (Ennett et al, 1999b;. The findings are mixed, however, in terms of which specific groups are higher or lower on the risk taking behaviors.…”
Section: Demographic Correlates Of Risky Behaviormentioning
confidence: 99%
“…Homeless young people have been defined as those between 12 and 24 years of age who have spent at least one night on the streets, in a public place (e.g., parks, under highway overpasses, abandoned buildings), or in a shelter (Greene & Ringwalt, 1997;Thompson, Safyer, & Pollio, 2001). The predominant focus of research with this youth population has been on the multitude and magnitude of their problems, including depression (Kennedy, 1991;Unger et al, 1998), anxiety (Kidd, 2004), suicide (Mallett, Rosenthal, Myers, Milburn, & Rotheram-Borus, 2004;Yoder, 1999), trauma (Thompson, 2005;Whitbeck & Simons, 1990), substance abuse (Lawrenson, 1997;Mallett et al, 2004;Thompson, 2004), school difficulties (Heinlein & Shinn, 2000), and legal problems (Mallett et al, 2004).…”
Section: Introductionmentioning
confidence: 99%